(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the satisfaction of international (Lao) patients receiving treatment at the International Department of 108 Military Central Hospital in 2025. Subjects and Methods: A cross-sectional descriptive study was conducted using a 5-point Likert scale to collect data from 207 inpatients treated at the International Department of 108 Military Central Hospital from January 2025 to December 2025. Results: Among 207 Lao patients, the highest overall satisfaction was observed in the domain of service outcomes (93.2%, mean score 4.55 ± 0.52/5), followed by healthcare workers’ attitude and professional competence (92.3%, 4.48 ± 0.58), facilities and infrastructure (91.8%, 4.40 ± 0.58), accessibility (89.8%, 4.19 ± 0.58), and the lowest in transparency of information and administrative procedures (84.5%, 4.03 ± 0.58). The highest-rated indicators included modern medical equipment (96.1%) and adequate hospital beds (95.7%). In contrast, lower satisfaction was reported for service costs (87.9%), hospital canteen services (85.0%), explanation of medical conditions (82.1%), and transparency of medication and treatment costs (80.2%). Multivariable logistic regression analysis revealed that a length of stay >7 days was associated with lower patient satisfaction (OR = 0.58; p = 0.01), whereas ≥2 treatment episodes were associated with higher satisfaction (OR = 2.47; p = 0.04). Conclusion: Lao patients reported a high level of satisfaction with treatment quality at the International Department of 108 Military Central Hospital. However, improvements in information transparency, cost management, and cafeteria services are needed to enhance the overall patient experience.